The development of relationships in science, technology, research and innovation in health between the EU and LAC countries: a promising future (RECIIS, 2014)
This paper presents the evolution of the dialogue between European Union and Latin American and Caribbean countries with regard to Science and Technology cooperation, especially in health. We begin with a historical overview and a periodization of the history of relations between these two regions referred by a system of Summits that strengthened and supported the political dialogue. Then, we identify existing instruments for EU-LAC relations in science and technology and the main areas of cooperation and – from this perspective – we analyzed the state of cooperation between the regions. Finally, we discuss the perspectives and next steps toward future relations between EU and LAC countries in science, technology, research and innovation in health. In the end of the paper we present the projections for the forthcoming EU-LAC cooperation in science and technology in health that are being worked in the EU-LAC Health initiative. Today the bi-regional relationship calls for mutual benefits and it is expected that the strategic partnership will add value to both regions.